1998
DOI: 10.1124/mol.54.6.1016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Glucocorticoid Response Element in the Rat β2-Adrenergic Receptor Gene

Abstract: Regulation of beta2-adrenergic receptor (beta2AR) levels by glucocorticoids is a physiologically important mechanism for altering beta2AR responsiveness. Glucocorticoids increase beta2AR density by increasing the rate of beta2AR gene transcription, but the cis-elements involved have not been well characterized. We now show that one of six potential glucocorticoid response elements (GREs) in the 5'-flanking region of the rat beta2AR gene is necessary for glucocorticoid-dependent stimulation of receptor gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…Dex influences testosterone synthesis and metabolism (Reznikov et al, 2004) and in turn, testosterone regulates the expression of a 2 ARs (Dygalo et al, 2002). Although parallel studies have not been conducted for sex-dependent effects on bAR expression, there are steroid-binding sites in the bAR promoter (Cornett et al, 1998), so that such differences may also exist for this receptor. In either case, the sexselective effects of Dex on adrenergic receptors and corresponding cell signaling during this critical period are likely to contribute to long-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dex influences testosterone synthesis and metabolism (Reznikov et al, 2004) and in turn, testosterone regulates the expression of a 2 ARs (Dygalo et al, 2002). Although parallel studies have not been conducted for sex-dependent effects on bAR expression, there are steroid-binding sites in the bAR promoter (Cornett et al, 1998), so that such differences may also exist for this receptor. In either case, the sexselective effects of Dex on adrenergic receptors and corresponding cell signaling during this critical period are likely to contribute to long-term effects.…”
Section: Discussionmentioning
confidence: 99%
“…The focused effects on adrenergic receptors may reflect a common origin in long-term hormonal effects of developmental Dex treatment. Both the a 2 AR and the bAR are directly regulated by hormonal input (Cornett et al, 1998;Davies and Lefkowitz, 1984;Dygalo et al, 2002), and it is therefore likely that the shift in hormone synthesis and metabolism that follows Dex treatment (Reznikov et al, 2004) contributes to the changes in receptor expression, in turn providing yet another factor that underlies the sex-selectivity of behavioral outcomes (Bowman et al, 2004;Kreider et al, 2005b).…”
Section: Neurotransmitter Receptor Bindingmentioning
confidence: 99%
“…36 It is suggested that a GC repressor domain in the rat b 1 -AR gene 37 may contribute to the transcriptional suppression of b 1 -ARs by GC. 36 Although b 1 -AR protein levels decline at 38 Although at present it is not known if catecholamine levels change at 0.9G compared to 0.5G in response to MNR, results of our study as well as those of others implicate a role for GC in regulating b-AR gene expression in fetuses of nutrient-restricted baboons.…”
Section: Discussionmentioning
confidence: 53%